2021
DOI: 10.1007/s10198-021-01366-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the additional costs of living with a disability in the United Kingdom between 2013 and 2016

Abstract: In the United Kingdom, more than 20% of the population live with a disability. Past evidence shows that being disabled is associated with functional limitations that often cause social exclusion and poverty. Therefore, it is necessary to analyse the connection between disability and poverty. This paper examines whether households with disabled members face extra costs of living to attain the same standard of living as their peers without disabled members. The modelling framework is based on the standard of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An extensive international literature base has been developed to estimate the extra costs of living with a disability. Several studies have used a standard of living approach, which is an indirect method designed to identify the changes in the relationship between income and utility to estimate the extra costs of living with a disability [10][11][12][13]. Schuelke et al (2021) compare the cost of living for households with disabled members and without disabled members in the UK and found that the average extra cost of living with a disability accounts for half of the median household income per week from 2013 to 2015 [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive international literature base has been developed to estimate the extra costs of living with a disability. Several studies have used a standard of living approach, which is an indirect method designed to identify the changes in the relationship between income and utility to estimate the extra costs of living with a disability [10][11][12][13]. Schuelke et al (2021) compare the cost of living for households with disabled members and without disabled members in the UK and found that the average extra cost of living with a disability accounts for half of the median household income per week from 2013 to 2015 [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have used a standard of living approach, which is an indirect method designed to identify the changes in the relationship between income and utility to estimate the extra costs of living with a disability [10][11][12][13]. Schuelke et al (2021) compare the cost of living for households with disabled members and without disabled members in the UK and found that the average extra cost of living with a disability accounts for half of the median household income per week from 2013 to 2015 [10]. Similarly, for the United States, Morris et al (2021) found that disabled households require 28% more income to obtain the same standard of living as a comparable household without a disabled member [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SOL approach has been used to understand disability-related costs in Cambodia, China, Ghana, Turkey, the United Kingdom (UK), the United States, and Vietnam [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Extra costs associated with disability have been found to vary by severity of impairment, employment status, and gender [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, disability-related expenses accounted for up to 23% of household incomes [ 12 ]. UK government transfer payments fell behind rising disability-related costs for households between 2013 and 2016 [ 14 ]. In Kenya, increased parenting stress was identified among poor households with a family member with disabilities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%